Об одном классе трехвалентных каузативных глаголов в литовском и английском языках - Карпувене, Г. (Kalbotyra, 1977)
The paper presents an attempt to analyse syntactical properties of some causative verbs in Lithuanian and English. The predicates of the given group take the following obligatory complements: Sub (subject), Obj (object), Med (means). Sometimes an argument is left out of the surface structure because it is subsumed as a part of the meaning of the predicate. For some verbs, however, if the usually omitted item needs to be delimited or qualified in some way, the entity can be mentioned.